Belgian firm, UPM in reseach venture - New Straits Times, Ooi Tee Ching (2010)
Desmet Ballestra, a Belgian process engineer, is collaborating with Universiti Putra Malaysia (UPM) to find competitive and energy-efficient ways to produce specialty fats.